1997
DOI: 10.1111/j.1365-2621.1997.tb04437.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, Sensory and Chemical Characteristics of Vacuum‐Packaged Cooked Beef Top Rounds Treated with Sodium Lactate and Sodium Propionate

Abstract: Cooked, vacuum-packaged beef top rounds containing 3% sodium lactate (NaL) or 3 or 4% NaL in combination with 0.1 or 0.2% sodium propionate (NaP) were stored for up to 84 days at 4ЊC. Addition of any of the treatments greatly reduced total Aerobic Plate Counts (APC). Positive flavor notes associated with fresh beef were enhanced by ingredient addition and tended to be highest in roasts with 3% NaL ϩ 0.2% NaP. Cooked roast beef color was enhanced by addition of NaL alone or in combination with 0.1% NaP. Lipid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…The increase in pH suggests that the observed effects of lactate on nitrite reactions were not due to pH effects on nitrite, because it is well-recognised that increased pH alone typically slows nitrite reactions in cured meat products (Cassens, 1990;Honikel, 2008). Other studies have reported that addition of sodium lactate increased meat pH (Maca et al, 1997;Papadopoulos et al, 1991b). Similarly, Kim et al (2009b) also found that steaks enhanced with lactate had higher pH values than non-enhanced steaks.…”
Section: Ph Determinationmentioning
confidence: 71%
See 1 more Smart Citation
“…The increase in pH suggests that the observed effects of lactate on nitrite reactions were not due to pH effects on nitrite, because it is well-recognised that increased pH alone typically slows nitrite reactions in cured meat products (Cassens, 1990;Honikel, 2008). Other studies have reported that addition of sodium lactate increased meat pH (Maca et al, 1997;Papadopoulos et al, 1991b). Similarly, Kim et al (2009b) also found that steaks enhanced with lactate had higher pH values than non-enhanced steaks.…”
Section: Ph Determinationmentioning
confidence: 71%
“…The addition of sodium or potassium lactate with a small amount of added water and salt (sodium chloride) can improve flavour, colour and tenderness of fresh meat, as well as increasing antimicrobial and antioxidant properties (Brewer, Rostogi, Argoudelis, & Sprouls, 1995;Kim, Keeton, Smith, Berghman, & Savell, 2009a;Kim et al, 2006;Maca, Miller, Maca, & Acuff, 1997;Papadopoulos, Miller, Acuff, Vanderzant, & Cross, 1991a;Papadopoulos, Miller, Ringer, & Cross, 1991b). Furthermore, lactate has consistently been shown to improve fresh meat colour by providing a strong antioxidant capacity (Kim, Huff-Lonergan, Sebranek, & Lonergan, 2010;Kim et al, 2009b) and increased metmyoglobin reducing activity (MRA) by elevating a reducing substrate (NADH) via increased lactate dehydrogenase (LDH) flux (Kim et al, 2006(Kim et al, , 2009bRodríguez, Kim, Faget, Rosazza, & Keeton, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…"Slight off-flavor" was detected in steaks treated with 2.0% NaL only and a combination of NaD and NaL (1.5 and 2.0%). Sodium lactate has been associated with off-flavor notes such as metallic, bitter, chemical, medicinal, sour, astringent, sodium, and salty (Papadopoulos et al, 1991;Williams et al, 1995;Maca et al, 1997). In general, researchers have reported that the off-flavor increases with increased usage levels of NaL.…”
Section: Sensory Evaluationsmentioning
confidence: 93%
“…Banks et al (1998) observed that yellowness in pork loin containing 1.0 to 2.0% NaL increased after 14 d of storage. Maca et al (1997) observed that raw ground beef patties became brighter, lighter, and more yellow with storage. The b* values recorded in this study were similar to those reported in the literature for fresh turkey breast meat (Werner et al, 2008).…”
Section: Objective Color Measurementmentioning
confidence: 95%
See 1 more Smart Citation